2021
DOI: 10.1016/j.arrct.2021.100102
|View full text |Cite
|
Sign up to set email alerts
|

How Well Does the Brief Interview for Mental Status Identify Risk for Cognition Mediated Functional Impairment in a Community Sample?

Abstract: Objective To determine the adequacy of the Brief Interview for Mental Status (BIMS) compared with other screening tools in identifying individuals with limitations in functional cognition and instrumental activities of daily living (IADL). Design Cross-sectional observational study. Setting Midsized midwestern city. Participants We assessed a convenience sample of community dwelling individuals (N=197) aged 55 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…This cross-sectional study uses data gathered as part of the Menu Task validation study ( Marks et al, 2020 , 2021a , b ; Al-Heizan et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…This cross-sectional study uses data gathered as part of the Menu Task validation study ( Marks et al, 2020 , 2021a , b ; Al-Heizan et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Relationships with MoCA scores and functional rehabilitation outcomes have been reported for patients with lower extremity amputations 5 and patients with hip fracture 1 . Recently Marks and colleagues (2021) found that the MoCA was more sensitive than the BIMS in predicting impairments in instrumental ADLs (iADLs; including checkbook balancing and shopping tasks) among older community dwellers 26 . Identification of patients who may have difficulty with functional and instrumental ADLs is important in creating a safe home discharge plan for patients and caregivers following an IRF stay.…”
Section: Introductionmentioning
confidence: 99%